The Utility of the Metacognitive Awareness Inventory for Teachers among In-Service Teachers - Heli Kallio; Kalle Virta; Manne Kallio; Arja Virta; Finn Rudolf Hjardemaal; Jostein Sandven (Canadian Center of Science and Education, 2022)
The purpose of the present study is to explore the utility of the compressed version of the Metacognitive Awareness Inventory for Teachers (MAIT-18) among in-service teachers. Knowledge of teachers’ awareness of metacognition is required to support students’ self-regulation, with the aim of establishing modern learning methods and life-long learning. The participants in this study were teachers (N = 208) from different sectors of vocational education. The data has been analysed using structural equation modelling. The Confirmatory Factor Analysis indicated good/acceptable model fit and convergence of each factor. Moreover, alpha scores of the inventory signify that the inventory is internally consistent. These findings reveal the utility of the MAIT-18 in measuring the Metacognitive Awareness of in-service teachers. Now, that the utility of the inventory has been examined among in-service teachers, comparative studies between in-service teachers and teacher trainees as well as longitudinal studies are prospective.